Gelatinous zooplankton diversity, distribution and seasonality in the northern Barents Sea and Arctic Ocean - Ciambelli, Angelo (UiT Norges arktiske universitet, 2023)
Gelatinous zooplankton, here referring to the phylum Cnidaria and Ctenophora and the class Appendicularia are important components of marine ecosystems due to their very diverse diets, life cycles and seasonal dynamics. In the Barents Sea, several studies reviewed the gelatinous zooplankton diversity, yet few studies documented the diversity and distribution patterns between the advected Atlantic Waters (AW) and Polar waters (PW) and no study reviewed the gelatinous zooplankton seasonality over a full year. The aim of this master thesis is to (1) investigate diversity and distribution patterns between the different water masses and regions of the northern Barents Sea and (2) investigate the gelatinous zooplankton seasonality over a whole year in the northern Barents Sea. For this purpose, during the Nansen Legacy project four seasonal surveys covered the full seasonal cycle of the Barents Sea marginal ice zone and collected both biological and physical data, including gelatinous zooplankton. Overall, 31 gelatinous zooplankton taxa were identified. Fritillaria borealis, Oikopleura sp. and Aeginopsis laurentii were the most abundant taxa and AW and PW influenced areas had different seasonal dynamics and composition, which were significantly influenced by the primary production, the zooplankton biomass, the inflow of AW and the latitudes. Keywords: Gelatinous zooplankton, Barents Sea, Seasonality, Distribution, Atlantic Waters, Polar Waters, Nansen Legacy